Empowering the Youth in Islamic Philanthropy: Cross-Cultural Perspectives and Global Experiences - Shofiyyah, Nilna Azizatus; Asep Muharam; Tedy Sutandy Komarudin; Dewi Rika Juita (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
This research analyzes the role and influence of Islamic philanthropy in empowering the youth across cultures. A qualitative research method with a literature study approach is employed. The study highlights the practices of Islamic philanthropy by youth from diverse cultural backgrounds and cross-cultural perspectives in their implementation. Global experiences also play a crucial role in empowering the youth. The findings of this research emphasize the importance of strengthening education and nurturing Islamic values to encourage youth involvement in philanthropy and promote cross-cultural interaction and collaboration to enhance their understanding and engagement in larger philanthropic initiatives.